Neoadjuvant Pyrotinib plus Trastuzumab and Chemotherapy for Stage I–III HER2‐Positive Breast Cancer: A Phase II Clinical Trial. (20th October 2020) - Xuhong, Juncheng; Qi, Xiaowei; Tang, Peng; Fan, Linjun; Chen, Li; Zhang, Fan; Tan, Xuanni; Yan, Wenting; Zhong, Ling; He, Cheng; Liang, Yan; Ren, Lin; et al.
Abstract: Lessons Learned: This is the first trial to explore the neoadjuvant therapy of pyrotinib in HER2‐positive operable and locally advanced breast cancer, in combination with epirubicin plus cyclophosphamide followed by docetaxel plus trastuzumab. Results primarily showed that pyrotinib in combination with epirubicin plus cyclophosphamide followed by docetaxel plus trastuzumab was effective and safe in HER2‐positive operable and locally advanced breast cancer. A subsequent randomized controlled trial is still warranted to confirm these results. Background: The efficacy and safety of neoadjuvant therapy of pyrotinib, a new irreversible tyrosine kinase inhibitor (TKI), was first estimated in patients with HER2‐positive breast cancer in this phase II study, in combination with trastuzumab and chemotherapy. Methods: Between February 19, 2019, and November 20, 2019, 20 female Chinese patients with stage I–III HER2‐positive breast cancer were assigned to receive eight cycles of neoadjuvant pyrotinib (P) in combination with four cycles of epirubicin (E) and cyclophosphamide (C) followed by four cycles of docetaxel (T) and trastuzumab (H), once every 3 weeks, referred to as P + EC‐TH. Results: A total of 19 patients completed the therapy and final surgery. The total pathological complete response (tpCR) rate was 73.7% (95% confidence interval [CI], 48.8–90.9), and no recurrence or metastasis occurred during the short‐term follow‐up period. The objective response rate (ORR) was 100% (95% CI, 82.4–100). The most common adverse events (AEs) were diarrhea and leukopenia in 18 of 20 patients (90%), but no grade 5 AEs were reported. Conclusion: This study showed that in HER2‐positive operable or locally advanced breast cancer, the tpCR rate of P + EC‐TH neoadjuvant therapy was about twice as high as that of EC‐TH neoadjuvant therapy reported in other trials, with tolerable side effects.